Migration and evolutionary analysis of trends in the transformation of maritime education in wartime conditions (Transport systems and technologies, 2024)
The research focuses on analyzing fundamental changes in Ukraine's higher education system occurring under the influence of unprecedented geopolitical events and demographic shifts, with particular emphasis on the maritime education sector. The study examines the period of 2020-2023, characterized by large-scale challenges caused by Russian military aggression and its consequences for the educational sector. Based on the analysis of institutional reports and statistical data, significant changes have been identified in student contingent dynamics, redistribution of educational flows, and transformation of educational practices. The research results demonstrate that despite considerable adaptability and successful implementation of European educational standards, Ukraine's higher education system has faced serious challenges related to forced youth migration and demographic decline. This problem is particularly acute in the maritime education sector, where there is a persistent trend toward decreasing numbers of students. The paper substantiates the necessity of systematic state measures for developing maritime education in Ukraine. The research reveals the complex interaction between demographic trends, educational transformation, and sectoral development under wartime conditions.
Keywords: adult higher education; Education during the war; Maritime Education and Training; competitiveness of education; educational migration; MET